One in, one out: The increase of EU legislation will lead to a crisis of enforcement - Jan Blockx (EconPol Forum, 2024)
The volume of legislation is increasing, also in the EU, but enforcement resources are not. This effectively means that in order to enforce new legislation, other legislation will need to be left unenforced: one in, one out. When introducing new rules that need to be enforced, legislators should therefore consider which older rules may go unenforced. This is particularly important for EU legislation as this usually relies on enforcement by the member states, making enforcement costs less visible.
Keywords: 330